Myopic Oligopoly Pricing - Iwan Bos; Marco A. Marini; Riccardo D. Saulle (Fondazione Eni Enrico Mattei (FEEM), 2021)
This paper examines capacity-constrained oligopoly pricing with sellers who seek myopic improvements. We employ the Myopic Stable Set stability concept and establish the existence of a unique pure-strategy price solution for any given level of capacity. This solution is shown to coincide with the set of pure-strategy Nash equilibria when capacities are large or small. For an intermediate range of capacities, it predicts a price interval that includes the mixed-strategy support. This stability concept thus encompasses all Nash equilibria and offers a pure-strategy solution when there is none in Nash terms. In particular, it provides a behavioral rationale for different types of pricing dynamics, including real-world economic phenomena such as Edgeworth-like price cycles, price dispersion and supply shortages.
Keywords: C72; D43; L13; 330; Behavioral IO; Bounded Rationality; Capacity Constraints; Oligopoly Pricing; Myopic Stable Set